Features of the art programs funded by the CHI in women over 40 years of age - D A Kuleshova; N Yu Melehova; T A Gustovarova; A N Ivanyan; A L Chernyakova; C B Krukovsky (IP Berlin A.V., 2016)
Purpose of the study is assessment of the effectiveness of the ART programs funded by the Compulsory Health Insurance Fund among patients older than 40 years of age. 80 ART programs at the expense of the mandatory health insurance funds (40 patients at the age of 40 and older, 40 patients younger than 40 years) have been analyzed. We have analyzed the data of the anamnesis, clinical and gynecological examinations, hormonal status, ultrasound scans, parameters of folliculogenesis in stimulation protocol, number and quality of the oocytes and embryos. There's a tendency of age-related decrease in number and quality of the embryos. The effectiveness of the ART programs in women of this age group is not high (20%), which requires an expansion of using the donor oocytes'cycles.